Serum Level of Anti-Hepatitis B Surface Antigen Among Students in Guilan, Iran - Yasaman Yaghobi; Iraj Nikokar; Hadi Sedigh Ebrahim-Saraie; Mojtaba Frahbakhsh; Mojtaba Safavi; Robabeh Ansar; Bahareh Fazli (Shiraz University of Medical Sciences, 2015)
Background: Hepatitis B virus (HBV) is considered as a serious public health concern. The health care workers and medical students are at a higher risk of HBV infection than the general population through occupational exposure. Vaccination against HBV is considered an effective means of infection prevention. Objectives: The aim of the present study was to determine anti-HBs titers among the medical students of Guilan University of Medical Sciences within the national HBV vaccination schedule. Patients and Methods: This cross-sectional study comprised 209 medical students born between the years 1989 - 92 within a national vaccination gap of HBV and received HBV vaccine before age 18 years. The levels of anti-HBsAg ≥ 10 mIU/mL detected by ELISA were considered as protective against HBV. Results: Of 209 students participated in this study, 11 (5.3%) showed no response to HBV vaccination. The protective titers of 10 - 1000 mIU/mL, and greater than 1000 mIU/mL of anti-HBs were found in 126 (60.2%) and 72 (34.5%) of students, respectively. Conclusions: The periodic monitoring of anti-HBs titers in medical students is important because of their awareness about the risk factors associated with HBV infection.